1972
DOI: 10.1016/0375-9474(72)90712-9
|View full text |Cite
|
Sign up to set email alerts
|

Shell-model calculations on the nickel isotopes

Abstract: Bmdang and excitation energies, electromagnetic transition rates and mult~pole moments have been calculated for 57-66N1 from many-particle shell-model wave functions with neutrons m the 2p@, lf~ and 2p½ orbits outside the S6N1 core The effective two-body matrix elements are obtmned from the modrfied surface deltainteraction The average absolute dewatmn between the calculated and experimental binding and excltatmn energies is 0.11 MeV (with the exclusion of 66NI) Electric quadrupole transmon rates and moments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Also, using the same reaction, the spectroscopic study by Ohnuma et al [35] excluded the 3060-keV cross-over transition. From the apparent lack of a cross-over transition, an ambiguous l = 2 assignment in the (p,t) angular distribution data for this state [36], and the shell model prediction by Glaudemans et al [3] for a 3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, using the same reaction, the spectroscopic study by Ohnuma et al [35] excluded the 3060-keV cross-over transition. From the apparent lack of a cross-over transition, an ambiguous l = 2 assignment in the (p,t) angular distribution data for this state [36], and the shell model prediction by Glaudemans et al [3] for a 3…”
Section: Resultsmentioning
confidence: 99%
“…The closure of both the 1f 7/2 proton and neutron shells in 56 28 Ni 28 leads to a simple shell-model description of the low-lying levels in the nickel isotopes with the proton shells completely inert and the valence neutrons in the 2p 3/2 , 1f 5/2 , and 2p 1/2 orbitals. Shell model calculations with this simple configuration space reproduce the energy spectra of the nickel isotopes up to ∼ 3 MeV [1][2][3]; however, calculations of electromagnetic transition rates do not reproduce the experimental values. This failure indicates the necessity for excitations of the 56 Ni core.…”
mentioning
confidence: 99%
“…Early shell model calculations [24] assumed closed proton and neutron shells at Z=N=28 and allowed the three valence neutrons to move in the lfs/2, 2pl/z and 2p3/2 orbits ('3p0h space'). This investigation showed that, within this model space, considerably modified transition operators were needed in order to reproduce the electromagnetic properties.…”
Section: Shell Model Calculations For S9nimentioning
confidence: 99%
“…(3) An experimental error in a static moment should be less than 10%. (4) Adopted values of a lifetime and a mixing ratio, or a B(E2) value deduced from them, must be consistent with results of other measurements. We have to relax these criteria somewhat for E2 transitions to collect a sufficient number of data.…”
Section: Determination Of Effective Operatorsmentioning
confidence: 90%